Effect of changes in tidal volume on multiple breath washout outcomes - Ratjen, Felix (PLoS One, 2019)
The lung clearance index (LCI), measured by multiple breath washout (MBW), reflects global ventilation inhomogeneity and is a sensitive marker of early obstructive airway disease. For the MBW test to accurately reflect a subject’s gas mixing within the lungs, the breathing pattern should represent physiologically appropriate tidal volumes (V(T)) and respiratory rate (RR). We aimed to assess whether changes in V(T) impact MBW outcome measures with a series of prospective and retrospective studies. MBW testing was performed using the Exhalyzer (®) D (EcoMedics AG, Switzerland). Healthy adult subjects performed MBW with uninstructed tidal breathing and a series of instructed tidal breathing tests, designed to isolate specific features of the breathing pattern. In addition, we retrospectively analyzed MBW data from two pediatric multi-centre interventional studies of cystic fibrosis (CF) subjects to determine the range of V(T) observed during uninstructed breathing, and whether breathing outside this range impacted results. The LCI was lower, but not significantly different between deep breathing at 20 ml/kg body weight and uninstructed tidal breathing; whereas LCI was significantly higher during shallow breathing compared with normal tidal breathing. For the majority of subjects with CF (80%), V(T) ranged from 9-15mL/kg. Within the observed V(T) range, LCI was similar in trials with mean V(T /)kg below this range compared to trials with V(T) /kg within the range. If subjects breathe naturally and are not instructed to use specific targets, the range of V(T) is within physiologically appropriate limits and normal variations observed do not impact MBW outcomes.